Dramaturgies of Love in Romeo and Juliet Word, Music, and Dance - Kellermann, Jonas (Taylor & Francis, 2021)
Bringing together current intermedial discourses on Shakespeare, music, and dance with the affective turn in the humanities, Dramaturgies of Love in Romeo and Juliet offers a unique and highly innovative transdisciplinary discussion of "unspeakable" love in one of the most famous love stories in literary history: the tragic romance of Romeo and Juliet. Through in-depth case studies and historical contextualisation, this book showcases how the "woes that no words can sound" of Shakespeare's iconic lovers nevertheless have found expression not only in his verbal poetry, but also in non-verbal adaptations of the play in 19th-century symphonic music and 20th- and 21st-century theatre dance. Combining methodological approaches from diverse disciplines, including affect theory, musicology, and dance studies, this study opens up a new perspective onto the artistic representation of love, defining amorous emotion as a generically transformative constellation of dialogic performativity. To explore how this constellation has become manifest across the arts, this book analyses and compares dramatic, musical, and choreographic dramatisations of love in William Shakespeare's early modern tragedy, French composer Hector Berlioz's dramatic symphony Roméo et Juliette (1839), and the staging of Berlioz's symphony by German contemporary choreographer Sasha Waltz for the Paris Opera Ballet (2007).